Team Functioning And Beliefs About Team Effectiveness In Inter-Professional Teams: Questionnaire Development And Validation - Kilpatrick, Kelley (J Multidiscip Healthc, 2019)
PURPOSE: Few validated instruments are available to measure team functioning in acute and primary care teams. To address this, we developed a questionnaire measuring healthcare provider perceptions of team effectiveness (Provider-PTE) and assessed its psychometric properties. PATIENTS AND METHODS: Empirical evidence and a conceptual model were used for item generation. The 41-item self-completed questionnaire was developed. A cross-sectional survey of healthcare providers (n=283) across a range of settings was performed. Psychometric properties were assessed for French and English language questionnaires using Cronbach alpha (α) for reliability, the feedback form for face validity, expert opinion for content validity, and the known-group technique for construct validity. Responsiveness was examined by comparing scores in high and low functioning teams. RESULTS: The mean time needed to complete the questionnaire was less than 9 mins. Respondents were typically female (84%), and employed full time (80%) in urban settings (82%). Cronbach α values were as follows: Team Processes = 0.88; PTE-Overall = 0.91; Outcomes = 0.72. Significant differences were found by professional group (p = 0.017), length of time in the team (p = 0.025), and presence of nurse practitioners. Responses to Outcomes varied by employment status (p = 0.017). Differences were identified in high and low functioning teams (p<0.001). Feedback indicated that two questions related to team meetings needed to be added. CONCLUSION: The study produced evidence of validity for English and French language Provider-PTE questionnaires. The revised 43-item instrument represents an important contribution by providing a validated questionnaire to measure team functioning across a range of settings that is consistent with a conceptual framework.